Accessing local electron-beam induced temperature changes during in situ liquid-phase transmission electron microscopy - Fritsch, Birk; Hutzler, Andreas; Wu, Mingjian; Khadivianazar, Saba; Vogl, Lilian; Jank, Michael P. M.; März, Martin; Spiecker, Erdmann (Nanoscale Advances, 2021)
A significant electron-beam induced heating effect is demonstrated for liquid-phase transmission electron microscopy at low electron flux densities using Au nanoparticles as local nanothermometers. The obtained results are in agreement with theoretical considerations. Furthermore, the impact of beam-induced heating on radiolysis chemistry is estimated and consequences of the effect are discussed.<br

Radiolysis‐Driven Evolution of Gold Nanostructures – Model Verification by Scale Bridging In Situ Liquid‐Phase Transmission Electron Microscopy and X‐Ray Diffraction - Fritsch, Birk; Zech, Tobias; Bruns, Mark; Körner, Andreas; Khadivianazar, Saba; Wu, Mingjian; Zargar Talebi, Neda; Virtanen, Sannakaisa; Unruh, Tobias; Jank, Michael; Spiecker, Erdmann; Hutzler, Andreas (Advanced Science, 2022)
Utilizing ionizing radiation for in situ studies in liquid media enables unique insights into nanostructure formation dynamics. As radiolysis interferes with observations, kinetic simulations are employed to understand and exploit beam-liquid interactions. By introducing an intuitive tool to simulate arbitrary kinetic models for radiation chemistry, it is demonstrated that these models provide a holistic understanding of reaction mechanisms. This is shown for irradiated HAuCl4 solutions allowing for quantitative prediction and tailoring of redox processes in liquid-phase transmission electron microscopy (LP-TEM). Moreover, it is demonstrated that kinetic modeling of radiation chemistry is applicable to investigations utilizing X-rays such as X-ray diffraction (XRD). This emphasizes that beam-sample interactions must be considered during XRD in liquid media and shows that reaction kinetics do not provide a threshold dose rate for gold nucleation relevant to LP-TEM and XRD. Furthermore, it is unveiled that oxidative etching of gold nanoparticles depends on both, precursor concentration, and dose rate. This dependency is exploited to probe the electron beam-induced shift in Gibbs free energy landscape by analyzing critical radii of gold nanoparticles.<br
Keywords: critical radius; gold nanoparticles; kinetic modelling; liquid-phase transmission electron microscopy; oxidative etching; particle growth; radiolysis